2013
DOI: 10.3390/metabo3040912
|View full text |Cite
|
Sign up to set email alerts
|

A Rapid Method for the Extraction and Analysis of Carotenoids and Other Hydrophobic Substances Suitable for Systems Biology Studies with Photosynthetic Bacteria

Abstract: A simple, rapid, and inexpensive extraction method for carotenoids and other non-polar compounds present in phototrophic bacteria has been developed. The method, which has been extensively tested on the phototrophic purple non-sulphur bacterium Rhodospirillum rubrum, is suitable for extracting large numbers of samples, which is common in systems biology studies, and yields material suitable for subsequent analysis using HPLC and mass spectroscopy. The procedure is particularly suitable for carotenoids and othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 49 publications
(75 reference statements)
0
19
0
Order By: Relevance
“…HPLC methods use isocratic and gradient mobile phases in either reversed-phase or normal-phase mode. Coupling a photodiode array detector to the HPLC allows for a continuous collection of spectrophotometric data during the analysis [23][24][25][26][27][28][29]. Much effort has been devoted to developing HPLC-mass spectrometry (HPLC-MS) methods with mainly atmospheric pressure ionization interfaces (APCI) or electrospray ionization interfaces (ESI) [30].…”
Section: Introductionmentioning
confidence: 99%
“…HPLC methods use isocratic and gradient mobile phases in either reversed-phase or normal-phase mode. Coupling a photodiode array detector to the HPLC allows for a continuous collection of spectrophotometric data during the analysis [23][24][25][26][27][28][29]. Much effort has been devoted to developing HPLC-mass spectrometry (HPLC-MS) methods with mainly atmospheric pressure ionization interfaces (APCI) or electrospray ionization interfaces (ESI) [30].…”
Section: Introductionmentioning
confidence: 99%
“…After some trials we found that a slightly modified mobile phase (98% MeOH/2% THF) was able to achieve acceptable resolution of the new carotenoids here, while maintaining the order of elution of the carotenoid intermediates described by Schwerzmann and Bachofen [17]. Typical HPLC profiles obtained using our modified mobile phase for hexane extracts obtained from both S1 (grown under semi-aerobic conditions to enhance the accumulation of carotenoid intermediates [2]) as well as the strain DP84 are shown in Fig. 7a.…”
Section: Hplc Analysismentioning
confidence: 92%
“…It has been shown previously, both by PCR-mediated gene shuffling, followed by expression in Escherichia coli [16], and high-level coexpression of different enzyme combinations in E. coli [1], that phytoene desaturase can also perform both 3,4-and 3 0 ,4 0 -desaturation. Recently, we have shown, using an R. rubrum crtD À mutant, ST4 [11], that phytoene desaturase, even at naturally occurring expression levels, can in fact perform both 3,4-and 3 0 ,4 0 -desaturation under conditions of limiting oxygen [2]. However, in all of these studies, the levels of carotenoids corresponding to these reactions are only minor, and the major carotenoid in the crtDmutant ST4 at the end of the growth phase is 3,4,3 0 ,4 0 -tetrahydrospirilloxanthin [11,2], which is the product of two sequential hydration and methylation reactions in the absence of 3,4,3 0 ,4 0 -desaturation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies propose a C18 column in combination with a wide variety of solvents e.g. studies used water-acetone mixtures [24,25], acetonitrile or hexane as extraction medium or solvent. All of the extraction solutions or solvents face the same problem that they are not equally suitable for all pigments.…”
mentioning
confidence: 99%